2013
DOI: 10.1371/journal.pone.0058798
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Genome Wide Association Studies of Alcohol Dependence: Support for Association with Variation in ADH1C

Abstract: Genome-wide association studies (GWAS) have revealed many single nucleotide polymorphisms (SNPs) associated with complex traits. Although these studies frequently fail to identify statistically significant associations, the top association signals from GWAS may be enriched for true associations. We therefore investigated the association of alcohol dependence with 43 SNPs selected from association signals in the first two published GWAS of alcoholism. Our analysis of 808 alcohol-dependent cases and 1,248 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The GRM used in all analyses comprised the 2596 unrelated individuals. Univariate and bivariate models were fitted to the phenotypic data while controlling for age, gender, study origin (to account for mean differences/batch effects between the different samples within SAGE), and the first five ancestral principal components to account for stratification effects within individuals of European descent (11). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GRM used in all analyses comprised the 2596 unrelated individuals. Univariate and bivariate models were fitted to the phenotypic data while controlling for age, gender, study origin (to account for mean differences/batch effects between the different samples within SAGE), and the first five ancestral principal components to account for stratification effects within individuals of European descent (11). …”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, molecular genetic studies have had limited success identifying individual genetic variants that are common across multiple substances of abuse (1-10). First, the primary conclusions from molecular genetic studies are that common single nucleotide polymorphisms (SNPs) modestly contribute to substance dependence phenotypes (e.g., rs1614972 in the alcohol dehydrogenase gene ( ADH1C) was the only replicable SNP in a recent alcoholism genome-wide association study (GWAS) (11), and variants in the CHRNA5-A3-B4 gene cluster have been repeated linked to tobacco addiction/dependence (12, 13)). Second, multiple genetic polymorphisms influence substance dependence.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of genome-wide studies (GWAS) have identified genetic variants associated with AD (321) . Studies suggest that associated variants are of small effect (17) and little overall heritability is explained by the sum of genome-wide significant SNPs (22, 23) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide association studies (GWAS) of SD traits have identified numerous significant risk alleles across the human genome [47]. Although replication studies and functional investigations have, in some cases, confirmed the role of these alleles in the predisposition to drug dependence [811], certain risk alleles have failed in replication efforts in independent study populations, likely due in part to the presence of heterogeneity and to other several confounding factors, including differences in ancestry in the samples being studied [12,13] (as well as, in some cases, the original results being false positives). Indeed, in studies of other complex phenotypes, including SD, there are three situations in which ancestry confounding effects are seen: genes significantly associated with the phenotype in one ancestry group, but not in other ancestry groups; genes associated with the phenotype in more than one ancestry group, but with different groups presenting specific associated alleles; and alleles associated with the phenotype in different ancestry groups with ancestry-related differences in association strength.…”
mentioning
confidence: 99%